Development of an IoT-Integrated Cigarette Smoke Detection System Using MiCS-5524 Sensor - Aminullah, Moh.Wahyu; Dina Fitria; Imam Akbar; Rama Denata (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Cigarette smoke is one of the primary causes of indoor air pollution, leading to various adverse health impacts. To address this issue, this research aims to design of a cigarette smoke detection device using the MiCS-5524 sensor integrated with the Internet of Things (IoT). This device can detect the level of cigarette smoke in indoor spaces and provide alerts through an LCD, a buzzer, and the Blynk application. Furthermore, the device can activate an exhaust fan to remove cigarette smoke from the room. The device employs the NodeMCU ESP8266 microcontroller as the central control unit for system operation and internet communication. The MiCS-5524 sensor was chosen for its high sensitivity to carbon monoxide (CO), a major component of cigarette smoke. Test results demonstrate that the device functions effectively and accurately in detecting cigarette smoke and responding to indoor air conditions. It is anticipated that this device will contribute to improving indoor air quality and human health.